ETUDE SOCIO-ECONOMIQUE s CONFLITS DES GUERRES ARMEES DANS LA VILLE DE KISANGANI ET SA PERIPHERIE EN PROVINCE DE LA TSHOPO (1997 A 2006) - Gabriel, KABUJI BUALU; Omer, NGBOLENGE TONGONZE (IJRDO - Journal of Social Science and Humanities Research, 2022)
The socio-economic study of the wars’ conflicts in Kisangani helped us the understand that was difficult to be developed when the peace is not. Kisangani town was being in a long very period in peace less from 1964-1965 with Muleste Rebellion, from 24 to 24 September 1991, brumpup the social movement of systematic steal of things violently in the Kisangani town. In 1997, the Kisangani town fell into AFDL’s hands ruled by the later “President Laurent Desiré KABILA”. The 23rd August 1998, Kisangani town fell too to the group of RCD’s troup (Congolese Reassembly for Democracy) from 5th to 10th June 2000, so’ was the six (6) days war, (APR), the Rwanda’s Army against (UPDF) the Ugandese Army, they quarreled about Kisangani town’s control, then more than 1000 death picked-up by the Read-coos of D.R.Congo. This the socio-economic study shows that we are in the self-consummation; the market as the coordinate mechanism between production and eatable demand is put out. But both of the market always intervene is linked in the implantation of markets the biggest, the poor meat, the linked of markets in the different ways of spring out.